Bridging Local Culture and Science Education: Interactive Engklek Game as a Tool for Enhancing Environmental Science Communication - Fadilla Kurniawati; Wahono Widodo; Hasan Subekti (International Journal of Emerging Research and Review, 2026)
Objective: Science communication skills are an essential competency for the 21st century, yet their teaching remains ineffective. Furthermore, local wisdom, such as the traditional game Engklek, has been largely eroded by technological developments and has not been optimized as a learning resource. This study aims to improve students' science communication skills on environmental pollution through interactive digital Engklek media based on local culture. Method: The study used a quantitative method with a quasi-experimental pretest-posttest control group design. The sample consisted of 64 seventh-grade students at State Junior High School 53 Surabaya, divided into an experimental class (learning with digital Engklek media) and a control class (conventional learning). The research instruments included a written science communication skills test and an oral communication skills observation sheet. Data were analyzed using the N-Gain test and the independent sample t-test. Results: The results of the study showed a significant increase in science communication skills in the experimental class (N-Gain=0.72; high category) compared to the control class (N-Gain=0.49; medium category). The independent t-test produced a significance value of 0.001 (<0.05), proving a significant difference between the two classes. Student responses to the learning media were also very positive.  Novelty: The novelty of this research lies in the digitization of the traditional Engklek game integrated with an ethnoscience approach, where each game box is designed as a stage in a scientific investigation of environmental pollution. This medium innovatively bridges local wisdom with modern pedagogy to build science communication skills in a contextual and enjoyable way.